2005
DOI: 10.1128/aem.71.9.5458-5464.2005
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Pasteurella multocida with Free-Living Amoebae

Abstract: Pasteurella multocida is a highly infectious, facultative intracellular bacterium which causes fowl cholera in birds. This study reports, for the first time, the observed interaction between P. multocida and free-living amoebae. Amoebal trophozoites were coinfected with fowl-cholera-causing P. multocida strain X-73 that expressed the green fluorescent protein (GFP). Using confocal fluorescence microscopy, GFP expressing X-73 was located within the trophozoite. Transmission electron microscopy of coinfection pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…Furthermore, bacteria such as E. coli O157:H7 (2) and S. enterica (34) are able to replicate inside the food vacuoles of protozoa. Similar results were reported with Pasteurella multocida (19), Mycobacterium avium (13), and L. pneumophila (18). This implies a complex role for protozoa in the ecology of human pathogens.…”
Section: Discussionsupporting
confidence: 78%
“…Furthermore, bacteria such as E. coli O157:H7 (2) and S. enterica (34) are able to replicate inside the food vacuoles of protozoa. Similar results were reported with Pasteurella multocida (19), Mycobacterium avium (13), and L. pneumophila (18). This implies a complex role for protozoa in the ecology of human pathogens.…”
Section: Discussionsupporting
confidence: 78%
“…are commonly found in natural aquatic systems, water supplies, and cooling systems (37, 50), usually feeding on bacteria (68). It was shown that amoebae host several intracellular pathogens including Legionella spp., Chlamydia spp., Parachlamydia spp., Listeria spp., Burkholderia spp., Campylobacter jejuni, Helicobacter pylori, Pasteurella multocida, Salmonella enterica, Francisella tularensis, and Simkania negevensis (10,32,38). The association, mentioned above, of Legionella pneumophila with Acanthamoeba spp.…”
mentioning
confidence: 99%
“…The fact that PMT also uses this evasion strategy suggests that it must be useful for the bacteria in some way. Pasteurella multocida is not a typical intracellular pathogen, however, the ability to invade host cells has been described in several publications [44,45,46,47,48,49,50]. However, whether toxigenic strains have an advantage in internalization or intracellular survival has not been studied yet.…”
Section: Pmt As a Potential Carcinogenmentioning
confidence: 99%